Early Cannabis Use and School to Work Transition of Young Men - Jenny Williams; Jan C. van Ours (Global Labor Organization (GLO), 2017)
We study the impact of early cannabis use on the school to work transition of young men. Our empirical approach accounts for common unobserved confounders that jointly affect se- lection into cannabis use and the transition from school to work using a multivariate mixed proportional hazard framework in which unobserved heterogeneities are drawn from a discrete mixing distribution. Extended models account for school leavers' option of returning to school rather than starting work as a competing risk. We find that early cannabis use leads young men to accept job offers more quickly and at a lower wage rate compared to otherwise similar males who did not use cannabis. These effects are present only for those who use cannabis for longer than a year before leaving school. Overall, our findings are consistent with a mechanism whereby early non-experimental cannabis use leads to greater impatience in initial labor market decision-making.
Keywords: C41; I12; J01; 330; multivariate duration models; discrete factors; cannabis use; job search; wages